The state's power to tax in the investment arbitration of energy disputes outer limits and the Energy Charter Treaty - Marian, Cornel (International arbitration law library ;, 2020)
"States today are expected not only to regulate the efficient and safe production and distribution of energy to end-users but also to incentivize increased production of energy and the transition to clean energy. In recent years, states are increasingly relying on taxation measures to address the economic challenges affecting the energy sector. This book provides the first in-depth exploration of the intersection between the treaty investment protection regime and taxation measures, as these materialize in investor-state energy disputes"--